Climate and farmers' willingness to pay for improved irrigation water supply. (December 2020) - Gebretsadik, Kidanemariam Abreha; Romstad, Eirik
Highlights: Climate change has significant and positive effect on farmer's willingness to pay. Socio-economic and marketing factors are also significant determinants of WTP. Irrigation access has insignificant effect on WTP. The findings indicate large scope for water pricing. The findings also shed light on where the expected benefits of irrigation are the largest. Abstract: Climate change in Eastern Africa increases water scarcity and raises the demand for additional water resources. To augment supply and adapt rainfall variability, most Sub-Saharan countries like Ethiopia emphasize the expansion of irrigation water supply, while paying less attention to the demand side in the management and use of water resources. Public investment on irrigation creates not only a strain on scarce public funds, but also is insufficient to utilize irrigation potential. Pricing (valuation) is a promising tool for efficient use of resources and cost recovery. Nevertheless, pricing of water (especially crop irrigation) has so far received little attention. Further, the effect of climate change on WTP for small-scale irrigation is not yet well investigated. Hence, this paper seeks to answer the applied part relating to local farmers' WTP for improved irrigation water supply. We control rainfall variability as a proxy for climate change, in which we support its reliability using the subjective assessment of respondents. We show that farmers are more willing to pay for improved irrigation water (up to 8% of their per capita income). Further, socio-economic, marketing, and climate change variables are found significant determinants of WTP. It suggests a large scope for water pricing and sheds light on where the expected benefits of irrigation are the largest. The findings might also fill the void in the literature and would pave for further research.